RHENIUM IN THE BLACK SEA: COMPARISON WITH MOLYBDENUM AND URANIUM - Colodner D.; Edmond J.; Boyle E. (My University, 1995)
Rhenium concentrations were measured in the Black Sea to determine the behavior of this redox-sensitive element in an anoxic basin. Under reducing conditions, Re is removed from solution, leading to its depletion from Black Sea deep waters. Compared with uranium, water column Re and Mo profiles show evidence of removal from mid-depths, suggesting that these elements are scavenged either in the water column or slope sediments to a greater degree than U. Black Sea surface waters are enriched in Re, reflecting Re in rivers draining into the northern Black Sea that are enhanced up to 80-fold over other large world rivers. This enrichment is most likely anthropogenic and may be due to coal burning in the region. A simple two-box model is used to demonstrate that Re concentrations in the Black Sea are not in steady state with respect to current riverine inputs and authigenic fluxes. Riverine inputs of U and Mo are not as significant, perhaps reflecting the fractionation of Re from the other elements during a high-temperature combustion process (Re2O7 is volatile above 270°C).